Role of Small and Medium Enterprises on Employment Provision in Uganda. A Case of Kabale Municipality. - Namanya, Moreen (Kabale University, 2023)
The study was about the Role of small and medium enterprises in employment provision in Uganda. A case study of Kabale Municipality. The objectives of the study were; to examine the financial capacity of SMEs in relation to employment provision in Kabale Municipality, to establish the management of SMEs in relation to employment provision in Kabale Municipality, and lastly; to assess the nature of SMEs in relation to employment provision in Kabale municipality. The study was carried out in Kabale municipality, in the Kabale district. The study adopted a cross-sectional research design with both quantitative and qualitative approaches. Out of 127 target samples expected to participate in the study, a total of 90 respondents actually participated giving a response rate of 70.8%. from objective one, the correlation coefficient r = .572** shows that there is a positive relationship between the Financial capacity of SMEs and Employment Provision in Kabale municipality. The implication of the correlation coefficient is that with a stable strong financial capacity of SMEs, there are many jobs created. Regarding The second objective of the study which aimed at establishing the management of SMEs in relation to employment provision in Kabale municipality, the study findings revealed that there was a significant positive relationship between the management of SMEs and employment provision in Kabale municipality at Pearson’s Correlation Coefficient (r = .836**). The researcher therefore concluded that improvement in the management of SMEs in Kabale municipality leads to an increase in employment provision. Lastly, Regarding the last objective of the study, findings revealed a positive relationship between the nature of SMEs and employment provision in Kabale municipality at Pearson correlation coefficient (r = .681**). The researcher therefore concluded that the nature of SMEs especially in terms of creditworthiness, and the size of the SME determines the number of people to employ in Kabale municipality.